Dynamic analysis of a vaulted dam - Benahmed, Abdelkrim; Bouguenina, Otbi; Meksi, Ali; Benmahdi, Khaled; Bendahane, Khaled; Sadoun, Mohamed (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The dynamic analysis of a seismic response of a concrete vault dam is a complex problem in which the representation of the behavior of the material requires some form of a nonlinear model, especially if the concrete is subjected to a significant stress load of the ground. In the case of large movements of the latter, large cracks may form in some areas of the dam, especially at the base of the dam and near sudden changes in geometry.  Methods: This analysis was based on a numerical simulation of the dynamic effect. This work was carried out using the finite element method with the ANSYS 12.1 program. The dam was modelled in two dimensions. Four types of analysis were performed: static analysis, modal analysis, seismic analysis under excitation of two accelerograms (Asnam 1980 and Boumerdes 2003), and spectral analysis.Results: This analysis showed the vulnerability of the Brezina dam to the Boumerdes earthquake with high stresses at the base of the structure.Conclusions: Based on this study, it was concluded that if the Brezina dam suffers an earthquake of a greater intensity than that of Boumerdes, this will cause structural damage and cracks that will compromise the dam’s watertightness as well as its durability.
Keywords: dynamic behavior; finite element method; cracking; dam; spectral analysis